Effect of virginiamycin on the performance and characteristics of swine carcass - Ribeiro, Ueliton Fernandes França; Kronka, Rodolfo Nascimento; Butolo, José Eduardo (Pesquisa Agropecuaria Brasileira, 2014)
Thirty pigs (Large White x Landrace x Wessex), fifteen castred males and fifteen females were utilized to study the effects of virginiamycin on the performance and characteristics of swine carcass. The results of weight gain, feed consumption and feed gain ratio were not statistically different among she levels of virginiamycin studied during pre-growing, growing and finishing phases. The results of carcass characteristics were not statistically different among the rations except for ham yield that was statistically significant (P<0.05) for sex. The females showed ham yield different (P<0.05) than the castred males (30.86% x 29.37%).